Investigation-action, inverted classroom and training based on skills. Key elements for effective b-learning training in management leadership (Innovaciones Educativas, 2020)
Faced with the challenge of having training approaches for practicing teachers and managers that address the complexities of the educational phenomenon, it is necessary to demonstrate the effectiveness of various training methodologies. The article describes the results of an investigation the objective of which was to determine the effectiveness of a course in leadership for innovation and change in school institutions, aimed at practicing teachers and school managers. The investigation also wanted to learn their assessment regarding the applied teaching strategy and its articulation with ICTs, by identifying factors of the training design that favor the transfer of learning to the educational context. For this, a quantitative methodology was used, through the application of a pre and post-test of knowledge to a sample of 168 course participants; and then a satisfaction survey applied in three cohorts, answered by 123 participants. The results show a statistically significant improvement in the participants’ knowledge of management skills, which evidenced the effectiveness of the course. On the other hand, the applied approach that guided the course, based on action research and the inverted classroom from a b-learning modality, was highly valued by teachers as it encourages applied and contextualized activities, autonomous work combined with collaborative reflection. This makes it possible to strengthen professional self-confidence, while favoring the subsequent transfer of learning.
Keywords: Continuing education; active teacher training; blended learning; managerial leadership; education; leadership